Pengaruh Project Based Learning (PJBL) untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Menggunakan Media Quizizz - Barus, Woyla Aurel Khairinnisa; Hasibuan, Eka Khairani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Using Quizizz media, this study intends to examine the substantial impact that Project Based Learning (PJBL) has on students' mathematical problem-solving skills in classes XI DKV 1 and XI DKV 2 at SMKN 1 Seberida. A quantitative approach combined with an experimental method is the methodology employed. All pupils in class XI DKV SMKN 1 Seberida, which consists of two classes, XI DKV 1 and XI DKV 2, made up the study's population. Two essay questions with markers of mathematical problem-solving skills served as the research tool. The study's findings demonstrated that students' ability to solve mathematical problems using Quizizz media was significantly impacted by the implementation of the Project Based Learning (PJBL) paradigm. In conclusion, students in classes XI DKV 1 and XI DKV 2 at SMKN 1 Seberida's mathematical problem-solving skills are effectively enhanced by the use of Project Based Learning (PJBL) supported by Quizizz media. Keywords: Project Based Learning, Mathematical Problem Solving, Quizizz